The Effect of A Proposed Training Program According to Maximal Achievement Level On The Development of Some Functional Indicators In Volleyball Players - Faraj, Dema; Salah, Talan (Journal of Physical Education, 2017)
The research aimed at identifying the differences in functional tests results between pre and posttests for both controlling and experimental groups for advanced volleyball players as well as identifying the differences in functional posttest results in controlling and experimental groups in advance volleyball players. The researchers used the experimental method. The subjects were (12) advance volleyball players. the subjects were divided into two groups; controlling that followed the traditional program and the experimental group that followed the proposed program. The data was collected and treated using proper statistical methods. The researchers concluded that using match – like training load improves functional indicators according to volleyball. Advance players should train according to a selected training program that is match – like and according to maximal time. Finally the researchers recommended using the proposed training program according to maximal performance time to develop functional indicators of advance volleyball players